Olea europaea leaves extract downregulate Newcastle disease virus gene expression in cancer cells - Salih, Rajaa Hindi (Iraqi Journal of Cancer and Medical Genetics, 2017)
Many researches have been made to find antiviral agents from natural sources. Leaf of Olea europaea (OLE) is one of themost important medicinal plants, as it is a well-known source of different phytochemicals. This study was carried out toinvestigate the effect of using Olea europaea leaves extract on the level of viral gene expression (M and F) in Hela cell line byusing the qRT-PCR. Also, we examined the adding of interferon-beta ( IFN-b ) as an antivirus factor and analyzed the expressionof viral and IFN-b genes to identify viral targets for OLE extract. First, we propagated the virus in embryonated chickeneggs and showed to kill embryos in different times intervals (less than 72 hours) with marked sever hemorrhage in infectedembryos, and agglutination activity reflects titer (1024) and 1×10 6.4 (TCID50). Hela cells were cultured and different concentrationof OLE extract was added; cell viability was measured by MTT assay. Gene expression showed that the expression ofthe viral gene was downregulated in the present of OLE extract. Pretreatment with IFN-b downregulated viral gene expressionhigher than the extract, also evaluated the IFN-b concentration by ELISA assay. OLE can be considered as antivirus agent andused this property to help in control Newcastle disease.